Co-encapsulação de Lactobacillus plantarum e compostos bioativos extraídos do caule de beterraba vermelha ( Beta vulgaris L.) por spray dryer - Deus, Cassandra de (2021)
This work aimed to investigate the influence, viability and stability of probiotic bacteria (Lactobacillus plantarum) microencapsulated with the aqueous extract of red beet stem at concentrations of 100% and 50%, using the spray drying technique. The microcapsules were evaluated during storage at different temperatures (25°C, 8°C and -18°C) for 120 days of both compounds, in addition to "in vitro" gastrointestinal simulations, heat treatment, as well as evaluation of the morphology and mean diameter of the microcapsules. It was found that the addition of the extract at a concentration of 100% adversely influenced the survival of probiotics, which also differed in size and morphological aspects compared to the control and the concentration of 50%. The best treatment containing probiotics and betalains was T5, where 50% of the extract was added, providing the viability of both compounds for a period of 120 days at different storage temperatures. Likewise, with regard to the protection of betalains, microencapsulation was promising compared to the control (free extract) which in less than a week ends up losing its color at 25 ºC and 8 ºC. Furthermore, the storage under freezing (-18 ºC) proved to be more efficient in the preservation of both compounds of interest. Finally, based on the obtained results, it can be concluded that the co-encapsulation of probiotics and beet stem extract was achieved, thus expanding the use of both compounds, minimizing property losses.